An investigation of visitors loyalty using formative and reflective measurements - Hossain, Enayet; Quaddus, Mohammed; Shanka, Tekle (Australian and New Zealand Marketing Academy, 2011)
This study was conducted for investigating visitors? loyalty using formative and reflective measurements at the destination level of Cox?s Bazar in Bangladesh. A conceptual model was developed and tested by a field study for making the model context specific. Then Partial Least Square (PLS) based Structural Equation Modeling (SEM) approach was used to test six hypotheses of proposed model on a sample of 602 visitors. Five hypotheses were supported at different significant levels. It is expected that the outcomes of this study will help the policymakers in tourism planning and implementing effective marketing strategies. Theoretically, this study will contribute in enhancing the causal relationships among formative and reflective constructs which have not been extensively studied yet in the tourism literature.